Wealth effects and the consumption of Italian households in the Great Recession - Renata Botazzi; Serena Trucchi; Matthew Wakefield (Institute for Fiscal Studies (IFS), 2013)
We estimate marginal propensities to consume from wealth shocks for Italian households. Large asset price shocks in 2008 underpin an IV estimator. A euro fall in financial or risky financial wealth resulted in cuts in annual total (non-durable) consumption of 5-9 (3.5-6) cents. There is evidence of effects for food spending. Responses of total and non-durable spending to changes in housing wealth are 0.2 to 0.4 cents/euro. Counterfactuals indicate financial wealth effects were important (relative to other factors) for consumption falls in 2008/09. Thus wealth effects on consumption can be important for households' welfare and aggregate outcomes.
Keywords: D12; D91; G01; 330; wealth effects; household consumption; 2008 crisis